Analisis Pertimbangan Mahkamah Konstitusi Dalam Perkara Nomor 49/PUU-XVI/2018 Tentang Presidential Treshold - Fajar Tri Laksono (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2019)
Law No. 7 of 2017 concerning General Elections Article222 governing the threshold of the nomination of president andvice president (presidential treshold). The Constitutional Courthas decided that the threshold for nominating a president andvice president is in accordance with the constitution. Thisresearch is categorized as library research with literaturestudy. The type of approach is legal normative. Considerationsof the Constitutional Court ruled that the threshold article(presidential treshold) is constitutional. First, the sound ofArticle threshold limits the political parties participating in thePresidential and Vice-Presidential Elections which have passedthe verification by the General Election Commission. Unfairtreatment is evident for participants in the general election,especially political parties who qualify to participate in thegeneral election and especially for those who want to run forpresident and vice president. Second, the implementation of thepresidential threshold is not appropriate to strengthen thepresidential system in Indonesia. Presidential Treshold is not aprerequisite for nomination, but a requirement for applying aminimum threshold for presidential election.Keywords: Presidential Treshold, Constitutional Court,Constitutionality